Predicative Possession in Northern Dialects of Khanty: Kazym, Shuryshkar, Priural and Tegi; Conference of the International Journal of Arts and Sciences; Vol. 11, iss. 3 - Vorobyeva V. V. Viktoriya Vladimirovna (2018, 2018)
Title screen